2021
DOI: 10.1007/s42452-021-04667-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between SARIMA and Holt–Winters models for forecasting monthly streamflow in the western region of Cuba

Abstract: The present study aims to compare SARIMA and Holt–Winters model forecasts of mean monthly flow at the V Aniversario basin, western Cuba. Model selection and model assessment are carried out with a rolling cross-validation scheme using mean monthly flow observations from the period 1971–1990. Model performance is analyzed in one- and two-year forecast lead times, and comparisons are made based on mean squared error, root mean squared error, mean absolute error and the Nash–Sutcliffe efficiency; all these statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…It is worth noting that models can have short-term and long-term predictive capabilities, with this study focusing on long-term predictions in line with the definitions of Mosavi et al [71]. The observed errors suggest that SARIMA models tend to be more reliable for longer-term forecasts, in line with the findings of Alonso Brito et al [72]. Additionally, the performance of SARIMA models is highly sensitive to the training time series used in model calibration, as highlighted by Danandeh Mehr et al [35].…”
Section: Discussionsupporting
confidence: 80%
“…It is worth noting that models can have short-term and long-term predictive capabilities, with this study focusing on long-term predictions in line with the definitions of Mosavi et al [71]. The observed errors suggest that SARIMA models tend to be more reliable for longer-term forecasts, in line with the findings of Alonso Brito et al [72]. Additionally, the performance of SARIMA models is highly sensitive to the training time series used in model calibration, as highlighted by Danandeh Mehr et al [35].…”
Section: Discussionsupporting
confidence: 80%
“…On the other side SARIMA model were found to be more reliable for longer lead-time forecasts. Hence, there is no general conclusion that places the models in a hierarchical order regarding their performance, it depends on the data used in the study [7].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on forecasting using these two methods have been conducted by researchers, such as [6], who predicted sales of clothing with seasonal data. In 2021, a comparison between SARIMA and Holt Winter's methods was conducted for the average monthly salary of a company in Cuba [7]. Other studies include forecasting energy consumption for smart grid operations [8], using SARIMA and LSTM on time series data, where the best model among the two methods produced the smallest error.…”
Section: Introductionmentioning
confidence: 99%
“…Its suitability relies on its accuracy in forecasting, as well as its flexibility and adaptability to a wide range of time series data, such as new car sales. Brito et al [35] concluded that the SARIMA models are more flexible in their application and more accurate in generating quality results.…”
Section: Literature Reviewmentioning
confidence: 99%